Copper-Mediated Synthesis of Monofluoro Aryl Acetates via Decarboxylative Cross-Coupling - Fahandej-Sadi, Anis; Lundgren, Rylan J. (Synlett, 2017)
We report the Cu-promoted oxidative cross-coupling of α-fluoromalonate half-esters and aryl boron reagents to deliver monofluoro α-aryl acetates under mild conditions (in air at room temperature). The reaction uses a simple, readily available monofluorinated building block to generate arylated compounds with functional groups that are not easily tolerated by existing methods, such as aryl bromides, iodides, pyridines, and pyrimidines.
Keywords: arylation; cross-coupling; copper; aerobic catalysis; fluorine